THE COMMA JOHANNEUM: A CRITICAL EXAMINATION OF ITS TEXTUAL AUTHENTICITY AND THEOLOGICAL SIGNIFICANCE - Edi Purwanto; Pieter Otta; Frans H. M. Silalahi (Manna Rafflesia, 2026)
The Comma Johanneum (1 John 5:7–8) has been the subject of significant debate within biblical studies and theology due to its explicit reference to the Trinity and its contested textual authenticity. This study critically examines the textual, historical, and theological dimensions of the Comma Johanneum through a comprehensive literature review. The research explores its presence in later Greek manuscripts, its prominence in the Latin tradition, and its role in Trinitarian theology. While opponents argue that the passage is a later interpolation based on its absence in early Greek manuscripts and its probable origin as a marginal gloss, proponents emphasize its doctrinal clarity, early usage by church figures, and inclusion in the Textus Receptus and the King James Bible. This study synthesizes these perspectives to affirm the Comma Johanneum’s theological significance while addressing the challenges posed by textual criticism. Ultimately, the research highlights the enduring relevance of the Comma Johanneum in discussions of Scripture preservation, doctrinal authority, and Trinitarian theology.